Intestinal Fatty Acid-Binding Protein as a Biomarker of Gastrointestinal Ischemia in Laparoscopic Surgery - Rizkinanto, Galih Surya; Santoso, Kohar Hari; Kriswidyatomo, Prihatma (Journal of Neonatal Surgery, 2025)
Laparoscopy is a widely used surgical technique noted for its safety, cost-effectiveness, and rapid recovery compared to laparotomy. However, it carries risks, particularly gastrointestinal complications, including gastrointestinal ischemia, which can arise from elevated intra-abdominal pressure (IAP) during procedures. This review discusses the role of intestinal fatty acid-binding protein (I-FABP) as a potential biomarker for detecting gastrointestinal ischemia in laparoscopic surgery. I-FABP, released from enterocytes upon injury, is a promising indicator of intestinal distress and has been linked to various gastrointestinal conditions. Elevated IAP during laparoscopy, essential for surgical visibility, can compromise organ perfusion and lead to ischemia, necessitating careful management. Monitoring I-FABP levels in high-risk patients could facilitate early detection and intervention, improving outcomes. This review underscores the need for further research to establish I-FABP’s clinical utility and to determine optimal monitoring protocols, aiming to enhance patient safety and reduce postoperative complications associated with gastrointestinal ischemia.